2019
DOI: 10.3892/ijo.2019.4809
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 5-FU and anti-EGFR antibody in combination with ASA on the spherical culture system of HCT116 and HT29 colorectal cancer cell lines

Abstract: The aim of this study was to examine the effects of 5-fluorouracil (5-FU), anti-epidermal growth factor receptor (EGFR) antibody and aspirin (ASA) on the characteristics of two CRC cell lines, HCT116 and HT29, maintained in a spherical culture system. We observed that the morphology of both the HCT116 and HT29 cell-derived spheres was significantly impaired and the size of the colonospheres was markedly reduced following treatment with the aforementioned three drugs. In contrast to adherent cultures, the spher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 85 publications
2
15
0
Order By: Relevance
“…In the HT-29 cell line, we found that CTX monotherapy could neither reduce the proliferation of tumor cells, nor inhibit the cell cycle and induce apoptosis, and in the detection of molecule phosphorylation rates, we found that knockdown or overexpression of EGFR in HT-29 cells did not cause significant changes in the downstream molecule phosphorylation rates of EGFR. In a study on gold nanoparticles, CTX-loaded nanoparticles did not significantly cause apoptosis in HT-29 cells compared to unloaded nanoparticles (36), and in HT-29 cells, the application of anti-EGFR antibody alone could not change the tumor cell spheroidization size or proliferation rate (37). These results are consistent with our research.…”
Section: Discussionsupporting
confidence: 90%
“…In the HT-29 cell line, we found that CTX monotherapy could neither reduce the proliferation of tumor cells, nor inhibit the cell cycle and induce apoptosis, and in the detection of molecule phosphorylation rates, we found that knockdown or overexpression of EGFR in HT-29 cells did not cause significant changes in the downstream molecule phosphorylation rates of EGFR. In a study on gold nanoparticles, CTX-loaded nanoparticles did not significantly cause apoptosis in HT-29 cells compared to unloaded nanoparticles (36), and in HT-29 cells, the application of anti-EGFR antibody alone could not change the tumor cell spheroidization size or proliferation rate (37). These results are consistent with our research.…”
Section: Discussionsupporting
confidence: 90%
“…A large number of studies confirmed that aspirin has a potential anti‐tumour effect; however, the application mechanisms underlying the application of aspirin combined with nano‐agents containing anti‐tumour drugs is not yet clear. Compared with the closest work related with aspirin in anti‐cancer treatment [36, 37], we used a novel nano‐drug delivery system to encapsulate both drugs and enhanced the cellular internalisation of drugs, thus showing higher uptake and increasing the therapeutic efficacy. In addition, we selected a non‐cytotoxic concentrations of aspirin (0.1 and 0.5 mM) to combine with 5‐Fu to evaluate its synergistic antitumour activity.…”
Section: Discussionmentioning
confidence: 99%
“…HT29 cells are human intestinal epithelial cells which produce the secretory component of immunoglobulin A (IgA) and carcinoembryonic antigen (CEA). HT29 cells are used for tumourigenicity studies [36,37]. HCT116 cells have been widely used in the study of biological characteristics of malignant tumor cells, the mechanism of anticancer drugs, and the screening of anticancer drugs.…”
Section: Discussionmentioning
confidence: 99%